GROWTH OF SHIGELLAE IN MONOLAYER TISSUE CULTURES - Gerber, Dolores F. (1961)
Gerber, Dolores F. (University of California, Berkeley) and H. M. S. Watkins. Growth of shigellae in monolayer tissue cultures. J. Bacteriol. 82:815–822. 1961.—The influence of environment on virulence, antigenicity, and antibiotic susceptibility of infectious agents is well recognized. The development of tissue culture monolayer techniques has stimulated new interest in manifestations of these attributes at the cellular level. Shigella flexneri and S. sonnei were grown intracellularly in Henle epithelial cell monolayer tissue cultures; uptake of the bacteria was induced by 50% normal horse serum in the infection medium. Since preliminary experiments indicated that streptomycin in the extracellular fluid depressed intracellular multiplication of these organisms, the antibiotic was later omitted from the tissue culture growth fluid. Extracellular multiplication of shigellae was controlled by thorough washing of the infected monolayers and replacement with fresh medium at 2-hr intervals during incubation. Intracellular growth patterns of two S. flexneri and two S. sonnei strains were established. Differences in the capacity of strains to adapt to the intracellular environment was reflected in the number of organisms subsequently produced, and appeared to be associated with the degree of intracellular resistance to streptomycin. No such variation was seen in cultures grown in broth. Microscopic examination of stained monolayers showed that intracellular bacterial growth was confined to the cytoplasm, which became filled with organisms prior to cellular disintegration. Biological implications of the variable response of Shigella strains to the intracellular environment are discussed.